Navigating English Teaching: Challenges and Strategies of Generation Z Teachers in the Digital Age - Ainiy, Lia; Sholah, Hanif Maulaniam (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This article explores the challenges and strategies that Generation Z teachers encounter in teaching English in the digital age. The method employed in this research is a case study approach, involving six English teachers from various schools as respondents. The objective of this research was to determine the challenges Gen Z teachers face in the English learning process and to explore their strategies for overcoming these obstacles. The findings reveal that Gen Z teachers face challenges, including classroom management issues, low student motivation, technological limitations, and the need to adapt to an independent curriculum. However, they can respond to these challenges through innovative strategies such as collaborative learning and gamification using digital technologies. Teachers also use platforms such as YouTube, TikTok, Google Classroom, and Quizizz to create interactive learning experiences that align with today's students' characteristics. This study highlights the unique role of Gen Z teachers as agents of change, who are adaptive, creative, and responsive to technological developments and the evolving needs of students. The findings provide essential input for education policy and the development of more contextualized teacher training.